USING BLOG TO INCREASE STUDENTS’ READING COMPREHENSION AT THE ELEVENTH GRADE OF SMA BATARA GOWA: An Experimental Research - Murniati; Nappu, Syamsiarna; Setiadi, Muhammad Astrianto (Journal of Computer Interaction in Education, 2018)
This research aimed to find out the improvement of the students’ reading comprehension by using Blog that focused on literal comprehension in term of main idea and interpretive comprehension in term of conclusion. The writer applied pre-experimental method with one group pretest-posttest design, and collected the data by giving pre-test and post-test. The sample of the research was class XI IPA of SMA Batara Gowa which consisted of 21 students. The sample was taken by using purposive sampling technique. The research findings showed that the eleventh grade students of SMA Batara Gowa had poor score in pre-test. After treatment, their reading comprehension was significantly increased. The result of the research were the mean score literal reading obtained by the students through pre-test was 69 and post-test was 77,2 with the t-test value main idea is greater than t-table (8,2> 2,08). Mean score interpretive reading pre-test 67, 3 and post-test 75 with the t-test value conclusion comprehension is greater than t-table (7, 6> 2, 08). The use of Blog increased literal comprehension in term of main idea and interpretive comprehension score in term of conclusion. Literal comprehension improved11, 8% and interpretive improved 11, 4%. The result of calculating t-test of the indicators in the students t-test reading comprehension (literal and interpretative comprehension) is greater than t-table 15, 8 > 2, 08. It means that there is significance difference between before and after giving the treatment).